2017
DOI: 10.36226/jrmb.v2is1.62
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemilikan Institusional Dan Struktur Modal Terhadap Nilai Perusahaan

Abstract: This study is aimed to examine the effect of institutional ownership and capital structure on the company’s value. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange from 2010 until 2014. The main data used in this research is the financial data in 2010 until 2014. Completed and selected financial data this research are 32 companies so that the samples in this research using five periods are 160. For examining data, this research uses panel data regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
33

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 3 publications
3
21
0
33
Order By: Relevance
“…While the results of research on the go public company (Aida and Rahmawati, 2015;Werastuti, 2014) and Indonesian go public banking (Hadiwijaya and Rohman, 2013) Intellectual capital has no significant effect on firm value. (Lestari, 2017) research found that intellectual capital has a negative effect on PBV in manufacturing companies listed on the IDX. (Sianipar, 2015) research found that income diversification has a positive effect on Return on Assets (ROA) of banks listed on the IDX.…”
Section: Introductionmentioning
confidence: 96%
“…While the results of research on the go public company (Aida and Rahmawati, 2015;Werastuti, 2014) and Indonesian go public banking (Hadiwijaya and Rohman, 2013) Intellectual capital has no significant effect on firm value. (Lestari, 2017) research found that intellectual capital has a negative effect on PBV in manufacturing companies listed on the IDX. (Sianipar, 2015) research found that income diversification has a positive effect on Return on Assets (ROA) of banks listed on the IDX.…”
Section: Introductionmentioning
confidence: 96%
“…Institutional investors are now emerging as an integral force in equity markets because they are important shareholders and are major players in developed markets and emerging markets (Tahir et al, 2015). According to Lestari, (2017) This study on institutional ownership is interesting to study. Some previous research results still show inconsistent research results such as Sujoko & Soebiantoro (2007), Bjuggren et al, (2007) found that institutional ownership has positive influence on company value.…”
Section: Introductionmentioning
confidence: 99%
“…The research. conducted by Lestari (2017) also found that institutional ownership has a positive effect on firm value. This shows the owner's control role is key to improving the companies performance.…”
Section: The Effect Of Institutional Ownership On Firm Valuementioning
confidence: 83%
“…There is inconsistency in research on institutional ownership, such as the study of Rustan et al (2014), Muryati & Suardikha (2014) and Lestari (2017) concluding that institutional ownership has a positive effect on firm value. But according to Warapsari & Suaryana (2016) and Sugiarto (2011) concluded that institutional ownership has a negative effect on firm value.…”
Section: Introductionmentioning
confidence: 99%